Caracterização comparativa entre soro autólogo e lisado plaquetário sob diferentes temperaturas e tempos de armazenamento - Camilo Ozorio Florez (2022)
Therapies with autologous serum and lysed platelet-rich plasma have shown promise among blood products and biological products. In ophthalmology, the autologous serum is a superior alternative to traditional eye drops in the treatment of eye diseases. Recently, lysed platelet-rich plasma (LP) has been considered a more interesting alternative treatment for multiple tissues because it has a lower unfavorable reaction than traditional PRP, which converts it into an interesting blood product to be used in ocular therapy. However, the veterinary literature does not provide a definitive comparison between the two, regarding the content of transforming growth factor-beta 1, proteins, and other important elements for use in ocular tissue, in addition to safety regarding contamination during a storage period. Thus, the objective of this study is to estimate the concentration of TGF-β1, one of the growth factors most involved in ocular therapy, as well as proteins with possible therapeutic function and possible bacterial contamination of autologous serum and lysed platelet-rich plasma in horses, over a storage period of 8 days. For the production of autologous serum, 63 ml of blood were collected per animal in 7 tubes of 9 ml without anticoagulant. For lysed PRP, 180 ml of blood were collected in 50 3.6 ml tubes with 3.2% sodium citrate. Processing was performed using techniques already established in the literature, in addition to modifications adapted in our laboratory, the two blood products were aliquoted into three vials, one of 1.5 ml and two of 0.5 ml for further analysis. For each of the treatments, one of the vials was destined for analysis by a commercial FC ELISA kit (TGF beta-1) and the other two, for the measurement of proteins and plating on blood Ágar, respectively, at the following time intervals storage time: 0, 4 and 8 days. The variables studied in this storage period were: CF concentration, protein profile (total protein and albumin) and bacterial growth expressed in colony-forming units (CFUs). The results obtained were submitted to normality tests. Where the comparison between the averages of the level of platelet, leukocyte, growth factor, proteins, and amount of CFUs was performed. The relevant findings were the relationship between basal platelets and the number of platelet concentrations in PRP; the correlation between growth factor and PRP-concentrated platelets; the greater amount of growth factor in LP; the higher amount of growth factor for the two products in the temperature storage group at 37°C, a higher concentration of serum proteins, both (PTT and albumin); in terms of bacterial contamination, we obtained results of greater contamination when the products were stored at 37°C and although the difference was not statistically significant, the LP had more contamination compared to the autologous serum.